RANCANG BANGUN KONTROL PID PADA SPEED OBSERVER GENERATOR DC BERBASIS ARDUINO UNO - M. Galih x Adi P.; Bambang Sri Kaloko (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
In this study discusses the development of observer to the generator speed direct current (DC) that is controlled using the rotary encoder sensor built using the Arduino UNO with recording capability of the two systems is also compared. Testing is done to see readings observer error indicates that the observer is sufficient with an average error of 0.81% of the speed sensor readings in this case be used as a standard. Application of PID control as the control of the speed observer DC generators that keep the generator speed setpoint despite the load current increases. Referring to the curve of speed and power relations in the prime mover speed setpoint is to improve the reliability and performance of the DC generator. PID control makes speed generator is stable at voltage setpoint. PID parameters used are Kp = 0.77, Ki = 0.0083 and Kd = 0.0096. After applying PID control value obtained rise time of 0.51 s, the steady-state error 1:28%. Testing is done by giving a resistive load to the setpoint speed of 1500 rpm, 2000 rpm and 3000 rpm and load variations that are used 50 Ω and 25 Ω. For steady-state error value obtained supreme 17:21% when the setpoint of 3000 rpm and the lowest was 0.004% at 2000 rpm setpoint. The highest value of recovery time on a setpoint of 3000 rpm that can not be returned to the setpoint and the lowest was 0.6 s current setpoint 1500 rpm. Keywords: Arduino Uno R3, DC Generator, PID, Speed Observer